THE URGENCY OF THE FAMILY'S ROLE IN FORMING CHILDREN'S CHARACTER IN DAILY LIFE - Putu Satya Narayanti; Gamar Abdullah; Indah Suciati, Dewi Sri Wahyuni, Hajerina (International Journal of Teaching and Learning, 2024)
The family is the smallest social unit that has an important role in forming national character. Family will shape a person's character and influence his environment because family is the first and main environment for character formation. The important role and quality of the family that colors character formation is the educational model given by parents to their children. The important role and quality of the family that colors character formation is the educational model given by parents to their children. Strengthening character for children is very important because the essence of a person's religion will be manifested in their morals. Positive characters that are instilled as early as possible, such as devotion to worship, good behavior, respect for parents, sincerity, humility and others, will slowly be internalized in children so that they ultimately have a positive impact on their mental and spiritual life. Informal education processes, especially families, both education regarding the character and morals of a child, the family plays the most important and first role. So that the formation of a child's character must be accompanied by the formation of good morals, especially from a religious perspective.